Printed Flexible Plastic Microchip for Viral Load Measurement through Quantitative Detection of Viruses in Plasma and Saliva - Shafiee, Hadi (Sci Rep, 2015)
We report a biosensing platform for viral load measurement through electrical sensing of viruses on a flexible plastic microchip with printed electrodes. Point-of-care (POC) viral load measurement is of paramount importance with significant impact on a broad range of applications, including infectious disease diagnostics and treatment monitoring specifically in resource-constrained settings. Here, we present a broadly applicable and inexpensive biosensing technology for accurate quantification of bioagents, including viruses in biological samples, such as plasma and artificial saliva, at clinically relevant concentrations. Our microchip fabrication is simple and mass-producible as we print microelectrodes on flexible plastic substrates using conductive inks. We evaluated the microchip technology by detecting and quantifying multiple Human Immunodeficiency Virus (HIV) subtypes (A, B, C, D, E, G, and panel), Epstein-Barr Virus (EBV), and Kaposi’s Sarcoma-associated Herpes Virus (KSHV) in a fingerprick volume (50 µL) of PBS, plasma, and artificial saliva samples for a broad range of virus concentrations between 10(2) copies/mL and 10(7) copies/mL. We have also evaluated the microchip platform with discarded, de-identified HIV-infected patient samples by comparing our microchip viral load measurement results with reverse transcriptase-quantitative polymerase chain reaction (RT-qPCR) as the gold standard method using Bland-Altman Analysis.